Internalisasi Sakinah Al-Qur'an sebagai Kerangka Dakwah Terapeutik Reduksi Anxiety - Aisy Nabila Fada; Abdul Malik Ghozali; Siti Badiah (IAIN Padangsidimpuan, 2026)
Anxiety has become a widespread psychological problem in modern society; however, existing da'wah studies have paid limited attention to formulating religious messages as a structured therapeutic framework to address this issue. This study aims to internalize the concept of sakinah in the Qur'an into a therapeutic da'wah message framework for reducing anxiety in modern society. Employing a qualitative approach, the research applies a thematic Qur'anic interpretation (tafsir maudhu'i) combined with content analysis of six Qur'anic verses on sakinah, supported by illustrative audience perception data regarding the effectiveness of the proposed message framework. The findings reveal that sakinah encompasses four therapeutic dimensions: cognitive, affective, spiritual, and social. These dimensions are synthesized into a five-stage therapeutic da'wah communication model, namely Identification–Relationship Building–Dhikr–Reflection–Action (IRZTA). The illustrative data indicate that the greatest perceived reduction in anxiety occurs within the spiritual and affective dimensions. The novelty of this study lies in developing a systematic procedure for transforming thematic Qur'anic interpretation into a structured and applicable therapeutic da'wah communication model. This model offers practical implications for religious counseling and digital da'wah content while contributing to the integration of Qur'anic and Tafsir Studies with contemporary communication psychology.